A call for congressional action: revisiting the U.S. coordinated framework for the regulation of biotechnology - Buchman, Leah; Kovak, Emma (Frontiers in Bioengineering and Biotechnology, 2025)
Since the 1986 release of the Coordinated Framework for the Regulation of Biotechnology almost 40 years ago, there have been two whole of government updates that made only minor changes, while new regulations and guidance from individual agencies have made more substantial alterations. Despite scientific advances and the emergence of products that fall outside the purview of legacy statutes, repeated calls for substantive changes have gone largely unanswered. We expand upon the NSCEB’s most important recommendations for improvements to the Coordinated Framework. We recommend that Congress create an NBCO and direct it to create a centralized application submission portal; conduct horizon scanning for future products of biotechnology; streamline regulations for familiar products and exempt low-risk products; and improve organizational structure, staff training, and interagency exchange.